Analisis Hasil Belajar Kognitif Siswa Pada Pembelajaran IPA Fisika Kelas X Sekolah Menengah Atas Dengan Pendekatan Konstruktivisme - Baiq Azmi Sukroyanti Yanti; Putu Budi Adnyana; I Gede Astra Wesnawa; I Putu Wisna Ariawan (Kappa Journal, 2024)
The aim of this research is to analyze students' cognitive learning outcomes in Physics subjects using a constructivist approach in class X of high school. This research uses a descriptive method with a qualitative approach. Data was collected through observation, interviews and documentation. Data analysis techniques involve three stages: data reduction, data presentation, and drawing conclusions. This research involved 32 students as research subjects. The results showed that 6 students got low scores, 15 students got medium scores, and 11 students got high scores. The highest score obtained by students was 100, while the lowest score was 65. The average student cognitive learning outcomes in Physics learning with a constructivist approach was 73,28, which is included in the currently category (55-74 interval). Based on these findings, it is recommended to use media and other innovative models in learning that can better support improving students' cognitive learning outcomes in class X physics learning in high school.